Diagnostics of hepatocellular cancer: state-of-the-art - T. Yu. Danzanova; G. T. Sinyukova; P. I. Lepedatu (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present features of hepatocellular carcinoma (HCC) diagnostics.Key points. Factors of HCC development, principles of screening diagnostics in risk group are discussed. The role of ultrasound investigation, X-ray, computer and magnetic-resonance tomography in HCC diagnostics is described, and also additional data which can be received with by radiological diagnostic methods that has high value in assessment resectability and preoperative surgical planning are reflected. The radiology is described at accompanying cirrhosis, difficulty of small HCC detection. Radiological differential diagnostics of HCC should be carried out with dysplastic nodules. Advantages and restrictions of each of method of visualization are presented.Conclusion. The issue of hepatocellular cancer diagnostics remains actual and requires further studies.